Evolutionary epidemiology of schistosomiasis: linking parasite genetics with disease phenotype in humans. Issue 2 (February 2018) - Huyse, Tine; Boon, Nele A.M.; Van den Broeck, Frederik; Mbow, Moustapha; Chaturvedi, Anurag; Meurs, Lynn; Volckaert, Filip A.M.; Polman, Katja
Graphical abstract: Highlights: A link between Schistosoma mansoni genetic variation in locus L46951 and human infection intensity was found. L46951 is located in a protein kinase gene that is linked with schistosome egg production. This genomic region therefore merits further functional research. Environmental association analysis is a powerful tool for molecular epidemiology. Abstract: Here we assess the role of parasite genetic variation in host disease phenotype in human schistosomiasis by implementing concepts and techniques from environmental association analysis in evolutionary epidemiology. Schistosomiasis is a tropical disease that affects more than 200 million people worldwide and is caused by parasitic flatworms belonging to the genus Schistosoma . While the role of host genetics has been extensively studied and demonstrated, nothing is yet known on the contribution of parasite genetic variation to host disease phenotype in human schistosomiasis. In this study microsatellite genotypes of 1561 Schistosoma mansoni larvae collected from 44 human hosts in Senegal were linked to host characteristics such as age, gender, infection intensity, liver and bladder morbidity by means of multivariate regression methods (on each parasite locus separately). This revealed a highly significant association between allelic variation at the parasite locus L46951 and host infection intensity and bladder morbidity. Locus L46951 is located in the 3′ untranslated region of the cGMP-dependent protein kinase gene that is expressed in reproductive organs of adult schistosome worms and appears to be linked to egg production. This putative link between parasite genetic variation and schistosomiasis disease phenotype sets the stage for further functional research.